Sustainable Horticultural Crops for a Permanent Agriculture - M.L.Dewan, (Journal of Soil and Water Conservation, 2022)
The ripe, golden grain fields had once been the symbols of well- being. But already in the period of the united world the unpredictability of annual plants and bushes has been partly replaced by perennial trees and bushes. There are thousands of different varieties of breadfruit, berries and nut fruit and bushes, each tree or bush producing hundreds of kilograms of protein – rich fruit. In his old age, Gandhi ji decided to start eating food that was only produced by trees. His decision demonstrated a very important point, which is also the main focus of Nutrition, Income Generation and Global Warming Reduction.